2022
DOI: 10.1063/5.0081061
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on asymmetric bubbles rising in water: Morphology and acoustic signature

Abstract: This study develops a three-dimensional imaging system to obtain comprehensive information on asymmetric bubbles formed in five nozzles with exits of the same cross section to examine the relationship between their patterns of flow and their acoustic characteristics. Acoustic signals of the bubbles were recorded by a hydrophone, and were analyzed through filtering and the short-time Fourier transform. The results show that the morphology of the bubbles became complex with increasing aspect ratio of the cross s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The rising of an isolated bubble in an unbounded configuration has been thoroughly investigated in the past [11][12][13] not only theoretically and numerically [14][15][16][17][18][19][20][21][22][23] , but also experimentally 15,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . However, most of these studies are focused on bubbles at low-Bond and high-Reynolds numbers, with the Bond number Bo = ρgD * 2 /σ and the Reynolds number a) Electronic mail: cestepa@ugr.es b) Electronic mail: cmbazan@ugr.es c) Electronic mail: rbolanos@ujaen.es Re = ρv * D * /µ, where ρ and µ the liquid density and viscosity, respectively, σ the surface tension, g gravity acceleration, D * the equivalent bubble diameter and v * the bubble terminal velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The rising of an isolated bubble in an unbounded configuration has been thoroughly investigated in the past [11][12][13] not only theoretically and numerically [14][15][16][17][18][19][20][21][22][23] , but also experimentally 15,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . However, most of these studies are focused on bubbles at low-Bond and high-Reynolds numbers, with the Bond number Bo = ρgD * 2 /σ and the Reynolds number a) Electronic mail: cestepa@ugr.es b) Electronic mail: cmbazan@ugr.es c) Electronic mail: rbolanos@ujaen.es Re = ρv * D * /µ, where ρ and µ the liquid density and viscosity, respectively, σ the surface tension, g gravity acceleration, D * the equivalent bubble diameter and v * the bubble terminal velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al [6] experimentally studied the relationship between nozzle interface shape and radiation noise characteristics, and found that elliptical nozzle produced the lowest noise level. Liu et al [7] studied the relationship between bubble morphology and acoustic characteristics under five different elliptic section nozzles by experiment. The results show that with the increase of the aspect ratio of the nozzle section, the bubble shape becomes asymmetrical, the center frequency of the bubble sound signal changes little, but the peak sound pressure decreases obviously.…”
Section: Introductionmentioning
confidence: 99%